The Relationship of Risk Factors to the Incidence of Pesticide Poisoning in Shallot Farmers in Batu Nona Hamlet, Anggeraja District, Enrekang Regency - Ronny; Mulyadi (Poltekkes Kemenkes Palu, 2025)
Background: The use of pesticides in agricultural activities is commonly practiced to increase productivity and protect crops from pest attacks. However, pesticide exposure can pose health risks to farmers, especially when not accompanied by adequate use of personal protective equipment (PPE), good personal hygiene, and proper attention to wind direction during spraying. These factors play an important role in preventing pesticide poisoning among farmers. this study aimed to determine the relationship between the use of personal protective equipment (PPE), personal hygiene, and spraying wind direction with the incidence of pesticide poisoning among shallot farmers in Batu Noni Hamlet, Anggeraja District, Enrekang Regency. Method: This research employed an observational design with a cross-sectional approach. The statistical test used was the Chi-Square test. The study sample consisted of 142 shallot farmers selected based on specific inclusion and exclusion criteria. Result: The results showed a significant relationship between the use of personal protective equipment (PPE) and pesticide poisoning (p = 0.001 < 0.05), personal hygiene and pesticide poisoning (p = 0.001 < 0.05), as well as spraying wind direction and pesticide poisoning (p = 0.001 < 0.05). Conclusion: There is a significant relationship between the use of personal protective equipment (PPE), personal hygiene, and spraying wind direction with the incidence of pesticide poisoning among shallot farmers. It is recommended that farmers increase awareness of the importance of using complete PPE, maintaining good personal hygiene, and paying attention to wind direction during spraying through participation in agricultural safety and health training programs.